2015
DOI: 10.1039/c4ra08195a
|View full text |Cite
|
Sign up to set email alerts
|

A facile electrochemical approach for the deposition of iron–manganese phosphate composite coatings on aluminium

Abstract: Cathodic electrochemical treatment is a facile approach for the deposition of iron–manganese phosphate composite coatings on Al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…75 The iron-manganese phosphate composite coating through cathodic electrochemical method revealed that the coating is dense and uniform, and the crystals of created coating are plane-shaped and diskshaped. 62 A similar morphology was also observed in chemical manganese phosphating method. 76,77 Sponge-shaped crystals have been observed in ironmanganese phosphate composite coating, such that after the ESD analysis, it was seen that they are in fact manganese-iron phosphate crystals.…”
Section: Phosphate Coating Mechanism Formation Through Anodic Electrosupporting
confidence: 70%
See 1 more Smart Citation
“…75 The iron-manganese phosphate composite coating through cathodic electrochemical method revealed that the coating is dense and uniform, and the crystals of created coating are plane-shaped and diskshaped. 62 A similar morphology was also observed in chemical manganese phosphating method. 76,77 Sponge-shaped crystals have been observed in ironmanganese phosphate composite coating, such that after the ESD analysis, it was seen that they are in fact manganese-iron phosphate crystals.…”
Section: Phosphate Coating Mechanism Formation Through Anodic Electrosupporting
confidence: 70%
“…In the case of manganese phosphate with the reduction of hydrogen ions on the surface of the cathode, the acidity value between cathode surface and electrolyte is reduced and the reaction for the formation of phosphate coating can be written as follows 62 :…”
Section: Phosphate Coating Formation Mechanism Via Cathodic Electrochmentioning
confidence: 99%
“…Meanwhile, the symmetric P 2p peak could be detected at 133.3 eV, which was characteristic of PO 4 3+ . 1 In addition, the Cr 2p spectra (Fig. 7F) displayed a nice resolve spin orbit doublet with two peaks (Cr 2p 3/2 and Cr 2p 1/2 ).…”
Section: Chemical Valence Of Pcc Ceramic Coatingsmentioning
confidence: 90%
“…Light-weight transport is considered ideal to reduce carbon dioxide gas emissions and to enhance the fuel economy. [1][2][3] In aerospace applications, owing to the low weight, high specic strength and better formability of aluminum (Al) alloys, they become the best candidate material to replace steel towards the development of a light-weight airplane. Especially, the 2A12 Al alloys have been widely used in various parts of the airplane, such as skin of the airplane, bulkhead of the airplane, wing ribs of the airplane, wing spars of the airplane, rivet of the airplane and so on, which is due to their low density, high fracture toughness and high thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation